Desain JaringaniFiberiToiThe HomeiTeknologiiGigabit Passive Optical Network (Gpon) Menggunakan Optisystem Untuk Area Sukawati - Diva Suryawan, I Putu; Sudiarta, P.K.; Sukadarmika, G. (Jurnal SPEKTRUM; Vol 6 No 3 (2019): Jurnal SPEKTRUM, 2019)
A Planning for fiber optic network using optical simulation from STO to ONT (optical Network Termination) with the farthest distance of ± 6.22 km done in the area of Jl. Batuyang, Kangin Batubulan, Sukawati, with an estimated number of customers of 270 customers aiming to switch networks from Multi Services Access Network (MSAN) to Gigabit Passive Optical Network (GPON). Planning starts from the survey area that will be built by the network, determines the customer's estimation, estimates the placement of the device and determines the specifications of the device to be used. Planning starting from STO to ONT / customer uses an optical application which will result from planning in the form of PRx on ODP (Optical Distribution Pack), PRx on ONT and bit error rate. The results of the analysis carried out, the Rx power generated in the ODP with the farthest distance of ± 6.22 km, which is for measuring results -26,893 dBm while in the planning results can be as much as -22,744 dBm, and PRx in ONT obtained for measuring results while in the planning obtained a result of -24.722 dBm, from the PRx results obtained the attenuation value is still below the ITU-T G.984 standard which is -28 dBm. BER value (Bit Error Rate) that is produced with the farthest distance of ± 6.12 km is 3,33x10?19 bit/s, this value is below the standard, namely 10?9 bit/s, with this result, optical fiber network planning using an optical system is feasible.